Errancias sexuales, errancias textuales: figuraciones literarias del siglo XXI - Arnés, Laura A. (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2019)
Being multi-directional, desire and passion force us not only to exist in this world in a different manner, but often, to inhabit different worlds. In this sense, I seek to explore the ways in which literary representations of sexuality set the stage to reflect upon the life of the body and the narratives in which it is reflected. This article aims to explore the ways in which the contingencies created by the contact among varied bodies provoke the re-organization of all sensitive surfaces (time, space, languages, literary genres, and gender itself) and build bodies that open themselves to an erratic sexuality and an unstable material existence, using contemporary works of Argentine literature such as El niño pez (Puenzo, 2004), Opendoor (Havilio, 2006), Me encantaría que gustes de mí and Dame pelota (Rosetti, 2005 and 2010). These bodies, thus, resist institutionalization, logic, and possible codes - including those which establish what is human.